Sublingual immunotherapy for pediatric allergic rhinitis: The clinical evidence - Poddighe, Dimitri (World J Clin Pediatr, 2016)
Allergic rhinitis is estimated to affect 10%-20% of pediatric population and it is caused by the IgE-sensitization to environmental allergens, most importantly grass pollens and house dust mites. Allergic rhinitis can influence patient’s daily activity severely and may precede the development of asthma, especially if it is not diagnosed and treated correctly. In addition to subcutaneous immunotherapy, sublingual immunotherapy (SLIT) represents the only treatment being potentially able to cure allergic respiratory diseases, by modulating the immune system activity. This review clearly summarizes and analyzes the available randomized, double-blinded, placebo-controlled trials, which aimed at evaluating the effectiveness and the safety of grass pollen and house dust mite SLIT for the specific treatment of pediatric allergic rhinitis. Our analysis demonstrates the good evidence supporting the efficacy of SLIT for allergic rhinitis to grass pollens in children, whereas trials regarding pediatric allergic rhinitis to house dust mites present lower quality, although several studies supported its usefulness.